A content analysis of school anti-bullying policies in Northern Ireland. Issue 3 (2nd July 2016) - Purdy, Noel; Smith, Peter K.
Abstract: This original study presents a content analysis of 100 primary and post-primary school anti-bullying policies in Northern Ireland using a 36-item scoring scheme. Overall schools had 52% of the items in their policies. Most schools included reference to physical, verbal, relational, material and cyberbullying but a minority mentioned racist, homophobic, sexual, adult/teacher–pupil bullying or bullying related to disability or religion. There was considerable variation in the source and quality of the definitions of bullying. Overall the policy scores compared favourably with earlier studies carried out in England, however a low percentage of Northern Ireland policies gave detailed information about how incidents of bullying would be recorded, who would coordinate this, and how the data would be used to evaluate the effectiveness of the policy. Findings are discussed in relation to the proposed new anti-bullying legislation currently being brought before the Northern Ireland Assembly.